Overloaded vertebral body: a unique radiographic phenomenon following multilevel anterior cervical discectomy and fusion - Chen, Shihao; Huang, Kangkang; Liu, Hao; Wu, Tingkui; He, Junbo; Yao, Minghe; Wang, Beiyu (Journal of orthopaedic surgery and research, 2023)
Purpose Because previous studies have not focused on postoperative cervical collapse, the purpose of the present study was to introduce the overloaded vertebral body (OVB) phenomenon following multilevel zero-profile anterior cervical discectomy and fusion (ACDF) as well as to investigate its effects on radiographic outcomes. Methods We conducted a retrospective study involving patients who underwent ACDF. A total of 55 patients were included in the analysis, including 110 OVB and 110 non-OVB. The evaluated vertebral parameters included the vertebral cross-sectional area (CSA), wedge angle (WA), vertebral height [anterior (AH) and posterior (PH)] and anterior-posterior vertebral diameter [upper (UD) and lower (LD)]. Results The CSA and WA were significantly lower in the OVB group than in the non-OVB group at 3, 6, and 12 months after surgery as well as at the final follow-up (p < 0.01). The AH of the OVB group was significantly lower at 3, 6, and 12 months after surgery as well as at the final follow-up compared to 1 week after surgery (p < 0.01). Conclusions OVB, a new phenomenon following multilevel ACDF, is defined as the cervical vertebral body located in the middle of the surgical segments in multilevel anterior cervical spine surgery. Statistical analysis of vertebral parameters, including CSA, WA, AH, PH, UD, and LD, showed that OVB occurs mainly at the anterior edge of the vertebra and that its largest radiographic manifestation is the loss of height at the anterior edge of the vertebra in the early postoperative period. Keywords: Overloaded vertebral body, Radiological outcomes, Anterior cervical discectomy and fusion, Three-level surgery